PENGEMBANGAN KOMPETENSI MAHASISWA BERDASARKAN LITERASI EKONOMI - Hutasuhut, Julianto; Putra Hrp, Ardhansyah; Andriyani Wirananda, Henny (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2024)
Economic literacy needs to be improved, especially for students who study economics so that they can make rational economic decisions. The purpose of this study was to determine and describe the level of economic literacy of students of the Faculty of Economics and Business, Al-Washliyah Muslim Nusantara University. The research method used is descriptive quantitative with a sample size of 76 people. The research instrument used is a test question of 20 questions. The data analysis technique uses the average calculation of the total answer score.The results of the study, the economic literacy level of Accounting Study Program students is higher than Management Study Program students, namely with a score of 74.29 compared to 73.82. Research findings, the highest average score of economic literacy level of Accounting Study Program students is about Economic Motives and Principles and Economic Actors, while the economic literacy level of Management Study Program students is about Trade, Exchange of Goods and Services. The economic literacy level of Accounting Study Program students with the lowest average score is about the Concept of Cost and Profit Maximization and Market Structure, while the lowest average score of Management Study Program students is about Money and Financial Institutions.In conclusion, the level of economic literacy of students is in the moderate category so that improvement efforts need to be made so that the quality of students' economic literacy can be further improved, especially on indicators whose average score is in the low category.